A Novel Design of CPW Feed Planar Omnidirectional Circularly Polarized Antenna - Jiawei Yang; Xi Li; Lin Yang (International Journal of Antennas and Propagation)
A novel planar omnidirectional circularly polarized (CP) antenna is presented. The omnidirectional circular polarization characteristics of the planar antenna are the result of the combined effect of a planar quasi-magnetic dipole (PQMD) and a printed electric dipole (PED) in this paper. The CP radiation pattern of the proposed antenna can be achieved by distributing appropriate current amplitude and phase to both elements, respectively. A power divider is used to adjust the amplitude and phase relationship between two basic components. In order to achieve a planar structure, coplanar waveguide (CPW) feed is adopted to feed the quasi-magnetic dipole for the first time. The overall electrical size of antenna is 1.61λ × 0.38λ. Finally, the correctness of our theoretical analysis is verified by processing and measuring this antenna. Through the analysis of the measurement results, we have obtained the following conclusions: the operating bandwidth of the proposed antenna obtained by measurement is from 5.67 to 5.86 GHz, in which the reflection coefficient is less than −10 dB and the axial ratio is less than 3 dB. Within the available bandwidth, the proposed antenna achieves omnidirectional radiation characteristics with a gain between 0.89 and 2.48 dBic.